Effect of resisted sled sprint with different loads on running velocity, step frequency, and step length in trained collegiate track and field athletes - Hamamichi, Takeru; Naoi, Kiyotaka; Shigeta, Susumu; Morais, Jorge; Marinho, Daniel Almeida; Moriyama, Shin-Ichiro (Motricidade, 2023)
Resisted sled sprint (RSS) is a traditional sprint training in which a variety of loads are used for multiple aims. Nevertheless, a detailed analysis of the effects of different loads has not yet been performed. Therefore, this study aimed to examine the effects of load differences on running velocity, step frequency, and step length during RSS in trained collegiate track and field athletes. Twenty-one collegiate track and field male athletes (20.6±1.3 years) performed eight 60-m sprints with and without a resisted sled. The sled loads were individually set based on the participant's body mass (BM) and were applied in 10% increments from 20% to 80% of BM. The running distance was divided into six 10-m phases. The mean running velocity, step frequency and step length at each phase, and interactions in each were analysed. All indices decreased with increasing loads. Significant differences were observed in running velocity and step frequency between all loads, except between 70% and 80% of BM, and in the step length between all loads. The maximum values for the variables appeared in different phases according to the load. These results suggested that athletes and coaches should consider that sprinting performance during RSS varies with load.